Wooclap como herramienta didáctica para el Aprendizaje de Biodiversidad del Ecuador: flora, fauna y especies en peligro de extinción con los estudiantes de sexto semestre de la carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Tipantasi Chauca, Jimmy Fabian (2024)
The research work emanates in the National University of Chimborazo in an enigma within which is focused, the apathy towards learning of the students of the sixth semester, period 2024 - 1s, of Pedagogy of Experimental Sciences, Chemistry and Biology of the Faculty of Sciences of Human Education and Technologies. The objective was to propose Wooclap as a didactic tool to contribute to the development of learning, which will help to effectively assimilate the subject under consideration. The methodology implemented was non-experimental design because the variables werenot altered, also a survey was used as an instrument applied to the population of 20 students, therefore, the approach is quantitative, and to give greater prominence to the information the research is descriptive, bibliographic and field research. As a result, it was found that the generality of the population totally agrees that the didactic tool, together with its use guide and interactivity, promotes a more efficient study, in short, Wooclap favors the assimilation of the contents of Biodiversity and Ecuador, Megadiverse country, thanks to the interactivity present, positively influencing the educational process. Therefore, it promotes the incorporation of diverse didactic tools in the educational space, which will contribute to a better understanding of the topics of study.